Buckling of double-walled carbon nanotubes - Elishakoff, Isaac; Dujat, Kévin; Lemaire, Maurice (Vietnam Journal of Mechanics, 2012)
In this note we deal with the approximate solution of the buckling problem of a clamped-free double-walled carbon nanotube. First the finite difference method is utilized to solve this case. Then this approach is verified by solving the buckling problem of a double-walled carbon nanotube that is simply supported at both ends for which the exact solution is available.